2011
DOI: 10.1016/j.molonc.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase related protein 1 (TYRP1/gp75) in human cutaneous melanoma

Abstract: Melanoma prognosis is based on specific pathological features at the primary lesion. In metastatic patients, the extent of lymph node involvement is also an important prognosis indicator. Many progression markers both in tissues and serum, including circulating tumor cells, have been studied and new molecular markers are awaited from high‐throughput screenings to discriminate between clinical stages and predict disease progression. The present review focuses on human tyrosinase related protein 1 also known as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 58 publications
1
66
0
Order By: Relevance
“…Mutations in the TYR or TYRP1 genes result in oculocutaneous albinism (OCA), a group of autosomal recessive disorders characterized by reduced production of melanin in skin, hair, and eyes, with OCA3 resulting from TYRP1 mutations. In addition, TYR and TYRP1 variants are significantly associated with risk of melanoma,5 a malignant tumor of melanocytes that, because of its aggressive nature, causes the majority of deaths related to skin cancer 6. Inhibition of melanogenesis may be an efficient therapeutic strategy, as evidenced by phase 1 clinical trials with a recombinant human monoclonal antibody against TYRP1 7…”
mentioning
confidence: 99%
“…Mutations in the TYR or TYRP1 genes result in oculocutaneous albinism (OCA), a group of autosomal recessive disorders characterized by reduced production of melanin in skin, hair, and eyes, with OCA3 resulting from TYRP1 mutations. In addition, TYR and TYRP1 variants are significantly associated with risk of melanoma,5 a malignant tumor of melanocytes that, because of its aggressive nature, causes the majority of deaths related to skin cancer 6. Inhibition of melanogenesis may be an efficient therapeutic strategy, as evidenced by phase 1 clinical trials with a recombinant human monoclonal antibody against TYRP1 7…”
mentioning
confidence: 99%
“…We recently demonstrated that elevated mRNA expression of tyrosinase-related protein 1 (TYRP1) 25,26 in metastatic melanoma biopsies correlates with poor overall patient survival [27][28][29] . Additionally, we and others have shown that the single-nucleotide polymorphism (SNP) rs683, located in one MRE-155 on the 3 untranslated region (3 UTR) of TYRP1, strongly reduces miR-155-induced decay 27,30 , thereby contributing to elevated levels of TYRP1 mRNA.…”
mentioning
confidence: 99%
“…The TYRP1 gene (NG_011705.1) consists of 8 exons and spans 16 kb genomic DNA on chromosome 9p23. The TYRP1 gene encodes a 537 amino acids tyrosinase-related protein 1 (TRP1) of about 60,724 Da (UniProtKB # P17643), is expressed in melanocytes and mainly localized within melanosomes, where it may regulate the melanogenesis [11]. Although, the TRP1 shares 93% homology to its mouse ortholog (tyrp1) [12], but significant differences are observed in their catalytic properties [13].…”
Section: Oca3mentioning
confidence: 99%
“…The exact catalytic function of TRP1 in melanin synthesis remains unclear. It forms a complex with tyrosinase that is important for normal intracellular trafficking and processing of tyrosine [14], as a result this complex may suppress the premature death of melanocytes by reducing the tyrosinaseinduced cytotoxicity [11]. However in OCA3, mutations in TYRP1 gene lead to the production of an abnormally short, nonfunctional TRP1 that is retained within the endoplasmic reticulum (ER).…”
Section: Oca3mentioning
confidence: 99%